Concentration-size dependences for the electron energy in AlxGa₁₋xAs/GaAs/AlxGa₁₋xAs nanofilms - Kondryuk, D.V.; Kramar, V.M.; Kroitor, O.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Using approximation of dielectric continuum and the Green function method,
studied in this work is the influence of electron-phonon interaction on position of the
bottom of the ground energy band for electron in the quantum well of a finite depth.
Considering the example of a plain nano-heterostructure with a quantum well based on
the double heterojunction AlxGa₁₋xAs/GaAs (nanofilm), the authors have calculated the
electron energy for a varied thickness of the film. It has been studied the influence of
barrier material composition as well as electron-phonon interaction on the electron
energy